Predictors of school satisfaction among adolescents in Jordan: a cross-sectional study exploring the role of school-related variables and student demographics - Saleh, Mohammad YN (J Multidiscip Healthc, 2019)
BACKGROUND: Understanding factors associated with adolescents’ satisfaction with school is necessary to enhance their physical and psychological well-being. PURPOSE: To investigate relationships among school-related variables, demographics, and school satisfaction and identify factors that predict school satisfaction among adolescents. METHODS: A cross-sectional descriptive design was used to recruit 1,200 Jordanian students aged 11–16 years. A multistage cluster-sampling technique was used to select participants, and the Health Behavior in School-Aged Children self-administered questionnaire was used to collect data. Data were analyzed using linear regression analysis to identify predictors of adolescents’ school satisfaction. RESULTS: Linear regression analysis showed that the adolescent’s satisfaction at school was predicted by age, male sex, teacher support, peer support, fair rules at the school, and tiredness in the morning. These factors explained 41% of variance in school-satisfaction scores. CONCLUSION: Social support at home and school were helpful for better satisfaction with school life among adolescents in Jordan.